Membrane partitioning of ionic liquid cations, anions and ion pairs – Estimating the bioconcentration potential of organic ions. (September 2017) - Dołżonek, Joanna; Cho, Chul-Woong; Stepnowski, Piotr; Markiewicz, Marta; Thöming, Jorg; Stolte, Stefan
Abstract: Recent efforts have been directed towards better understanding the persistency and toxicity of ionic liquids (ILs) in the context of the "benign-by-design" approach, but the assessment of their bioaccumulation potential remains neglected. This paper reports the experimental membrane partitioning of IL cations (imidazolium, pyridinium, pyrrolidinium, phosphonium), anions ([C(CN)3 ] −, [B(CN)4 ] −, [FSO2 )2 N] −, [(C2 F5 )3 PF3 ] −, [(CF3 SO2 )2 N] − ) and their combinations as a measure for estimating the bioconcentration factor (BCF). Both cations and anions can have a strong affinity for phosphatidylcholine bilayers, which is mainly driven by the hydrophobicity of the ions. This affinity is often reflected in the ecotoxicological impact. Our data revealed that the bioconcentration potential of IL cations and anions is much higher than expected from octanol-water-partitioning based estimations that have recently been presented. For some ILs, the membrane-water partition coefficient reached levels corresponding to BCFs that might become relevant in terms of the "B" (bioaccumulation potential) classification under REACH. However, this preliminary estimation need to be confirmed by in vivo bioconcentration studies. Graphical abstract: Highlights: Both cations and anions can have a strong affinity for phosphatidylcholine bilayer. Bioconcentration potential of ILs is much higher than expected from log Kow . The log KMW of long-chain ILs (≥C14) indicates "B" classification. BCF of organic ions is dependent on environmental conditions. Abstract : Our preliminary correlation of membrane-partition coefficients vs. BCF clearly demonstrated that the bioconcentration potential of IL cations and anions is much higher than expected from octanol-water partitioning.